2022
DOI: 10.1002/ptr.7527
|View full text |Cite
|
Sign up to set email alerts
|

Heilaohuacid G, a new triterpenoid from Kadsura coccinea inhibits proliferation, induces apoptosis, and ameliorates inflammation in RA‐FLS and RAW 264.7 cells via suppressing NF‐𝜅B pathway

Abstract: Heilaohu, the roots of Kadsura coccinea, has been used in Tujia ethnomedicine to treat rheumatic arthritis (RA). Heilaohuacid G (1), a new 3,4‐seco‐lanostane type triterpenoid isolated from the ethanol extract of Heilaohu, whose structure was determined using HR‐ESI‐MS data, NMR spectroscopic analyses, and ECD calculations. In this study, our purpose is to elucidate the mechanisms of Heilaohuacid G in the treatment of RA by inhibited proliferation of rheumatoid arthritis‐fibroblastoid synovial (RA‐FLS) cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Heilaohuacid G ( 19) is a new 3,4-seco-lanostane type triterpenoid isolated from the roots of Kadsura coccinea, a medicinal plant distributed in South China and used in Tujia ethnomedicine to treat RA [100]. Biological activity screening tests revealed that 19 inhibited the proliferation of RA FLSs in a concentration-dependent manner, with IC 50 values of 8.16 ± 0.47 µM [100].…”
Section: Tetracyclic and Rearranged Triterpenesmentioning
confidence: 99%
See 3 more Smart Citations
“…Heilaohuacid G ( 19) is a new 3,4-seco-lanostane type triterpenoid isolated from the roots of Kadsura coccinea, a medicinal plant distributed in South China and used in Tujia ethnomedicine to treat RA [100]. Biological activity screening tests revealed that 19 inhibited the proliferation of RA FLSs in a concentration-dependent manner, with IC 50 values of 8.16 ± 0.47 µM [100].…”
Section: Tetracyclic and Rearranged Triterpenesmentioning
confidence: 99%
“…Heilaohuacid G ( 19) is a new 3,4-seco-lanostane type triterpenoid isolated from the roots of Kadsura coccinea, a medicinal plant distributed in South China and used in Tujia ethnomedicine to treat RA [100]. Biological activity screening tests revealed that 19 inhibited the proliferation of RA FLSs in a concentration-dependent manner, with IC 50 values of 8.16 ± 0.47 µM [100]. Further studies showed that 19 induced RA FLS apoptosis and suppressed inflammatory responses in LPS-induced RA FLSs and macrophages (RAW264.7 cells) by inhibiting NF-κB signaling [100].…”
Section: Tetracyclic and Rearranged Triterpenesmentioning
confidence: 99%
See 2 more Smart Citations
“…The immense potential of natural products in treating various diseases, including OA, has been a continuous exploration. Notably, key findings from current research underscore the promising role of natural products in mitigating OA symptoms, potentially influencing macrophage behavior and inflammatory responses within the joint microenvironment (7,8). Crucially, alkaloids, widespread in nature (9), play a key role in Traditional Chinese Medicine's therapeutic effects, exhibiting significant anti-cancer, anti-inflammatory, and antioxidant activities (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%